Comparative Side Effects of Carbetocin vs Oxytocin in Prevention of Postpartum Bleeding Following Cesarean Sections - Tarin, Ayesha Uzaima; Rasheed, Maria; Amin, Sadia (Biological and Clinical Sciences Research Journal, 2025)
Postpartum hemorrhage (PPH) remains one of the leading causes of maternal morbidity and mortality worldwide. Uterotonic agents such as oxytocin and carbetocin are commonly administered during cesarean sections to reduce the risk of PPH; however, their comparative safety and hemodynamic effects require further evaluation. Objective: To compare the side effects and hemodynamic effects of carbetocin versus oxytocin for preventing postpartum bleeding in women undergoing cesarean sections. Methods: This prospective study was conducted in the Department of Gynecology and Obstetrics, Nishtar Hospital, Multan, from November 5, 2024, to May 5, 2025. A total of 300 women undergoing elective cesarean section at term with singleton pregnancies and no comorbidities were enrolled using a convenience sampling technique. Participants were randomly assigned into two groups: the control group (n=150) received 5 IU of oxytocin intravenously over 3 minutes followed by a continuous infusion of 10 IU in 1000 mL Plasma-Lyte over 24 hours, while the study group (n=150) received 100 μg of carbetocin intravenously over 3 minutes followed by 1000 mL Plasma-Lyte infusion over 24 hours. Primary outcomes included the incidence of side effects (nausea, vomiting, flushing) and hemodynamic parameters (heart rate, blood pressure, hemoglobin, and hematocrit levels). Statistical analysis was performed using chi-square and t-tests, with a p-value <0.05 considered significant. Results: The incidence of side effects was comparable between the groups: 22% in the carbetocin group and 21% in the oxytocin group. Nausea occurred more frequently in the oxytocin group (14%) than the carbetocin group (8%), while flushing was more frequent in the carbetocin group (14%) compared to the oxytocin group (8%); however, differences were not statistically significant (p>0.05). No patients in the carbetocin group required additional uterotonics or antiemetics. The mean postoperative hemoglobin drop was 2.15 g/dL in the carbetocin group and 2.2 g/dL in the oxytocin group (p=1.0), and the hematocrit change was also similar (p=0.9), indicating no significant hemodynamic difference between the two agents. Conclusion: Carbetocin and oxytocin demonstrate similar efficacy and safety profiles in preventing postpartum hemorrhage in cesarean deliveries, with no significant differences in side effects or hemodynamic outcomes. Carbetocin may offer a slight advantage by reducing the need for additional uterotonic or antiemetic therapy.